Comparative inflammatory effect of antiseptic irrigating solutions against conventional irrigation with sodium chloride in rats. - Rodríguez Alfaro, Miguel (2010)
The aim of this study was to demonstrate that the use of irrigating solutions in surgical procedures does not alter both inflammation processes and tissue repair. Four (04) groups were formed containing 15 rats each. After being dosed with general anaesthesia, they underwent osteotomy in the tibia with tungsten carbide burs and irrigation for 15 seconds, using the following solutions in each group: A) 0,12 % chlorhexidine with cetylpyridinium 0,05 %, B) 0,12 % chlorhexidine with aspartame; C) hexetidine 0,1 %; D) 0,9 % sodium chloride. After 3, 7 and 15 days of surgery, the rats were sacrificed and tissue samples were removed for histopathological analysis. The results showed that groups in which chlorhexidine with cetylpyridinium, and chlorhexidine with aspartame were used, less inflammatory process were found than in groups of sodium chloride and hexetidine. On the process of tissue repair, the 4 groups followed a similar pattern, although the group in which hexetidine was used showed up an restoration much more intense after 7 and 15 days. It led to conclude that the use of chlorhexidine with cetylpyridinium and chlorhexidine with aspartame decreases the postoperative inflammatory process in contrast to other groups, while the tissue repair process was similar in all groups, with greater intensity after 7 and 15 days of hexetidine group.